DYNAMICS OF NEMATODE MANAGEMENT IN ENHANCING THE POTATO PRODUCTION - Krishna Prasad, K S (Potato Journal, 2013)
Potato is an integral part of Nilgiris agricultural activities, which sustains the economy of this region. Unlike other parts of the country, the farmers in this region remain active almost round the year with the agricultural activities due to the equinox climate with well-distributed rains. This situation helps the farmers to grow potato almost through out the year. This however, also perpetuates persistent problems of potato. Among them the potato cyst nematodes (PCN) and the late blight disease form the core of this matrix while tuber moth and brown rot are in the periphery.